Vaccination against human papillomavirus (HPV) as primary prophylaxis of cervical cancer and other lesions induced by HPV - Majewski, Sławomir; Sikorski, Marek (Przewodnik Lekarza/Guide for GPs, 2008)
In the article new data on anti-HPV vaccines are presented including their immunogenicity and clinical efficacy in prevention of cervical dysplasia and cervical cancer as well as vulvar premalignant and malignant lesions and other HPV-associated diseases (e.g. genital warts). In addition data on safety of the vaccines are presented and the possibility of cross-protection is discussed.